A Step Forward in the Conceptualization and Measurement of Parental Burnout: The Parental Burnout Assessment (PBA) - Roskam, Isabelle; Brianda, Maria-Elena; Mikolajczak, Moïra (Frontiers in Psychology, 2018)
So far, the conceptualization and measurement of parental burnout have been deduced from those of job burnout. As a result, it is unclear whether current measures of parental burnout constitute the best representation of the parental burnout construct/syndrome: the possibility cannot be excluded that some dimensions ought to be added, which would change the structure and definition of parental burnout. In this study, the conceptualization and measurement of parental burnout were approached using an inductive method, in which the parental burnout phenomenon was (re)constructed based solely on the testimonies of burned-out parents. Items extracted from their testimonies were presented to a sample of French-speaking and English-speaking parents (N = 901) and submitted to factor analyses. An identifiable parental burnout syndrome including four dimensions was found (exhaustion in one’s parental role, contrast with previous parental self, feelings of being fed up with one’s parental role and emotional distancing from one’s children). The resulting instrument, the Parental Burnout Assessment (PBA) presents good validity. Factorial invariance across gender and languages was also found. Finally, the results of this study replicate previous findings that psychological traits of the parents, parenting factors and family functioning account for more variance in parental burnout than sociodemographic factors.